Solid state physics essential concepts - Snoke, D. W. (Cambridge University Press, 2019)
"This book centers on essential theoretical concepts in all types of solid state physics, using examples from speci c systems with real units and numbers. Each chapter focuses on a di erent set of theoretical tools.